Wajah IAIN Surakarta di Mata Masyarakat Pucangan - Abdul-Rauf, Shofwan Anwar (SHAHIH: Journal of Islamicate Multidisciplinary, 2017)
This study aims at describing the Pucangan society in Kartasura district towards IAIN Surakarta. High education influences social change either positive or negative effects. This study employs the qualitative method, whereas main sources of this research take for granted derived from Pucangan society, which is interviewed. This study looks at instituteâs influences from many aspects such as religion, social, economics, and education. The results show Pucangan society perception towards IAIN Surakarta existence, so there must be an effort to establish a positive image of IAIN Surakarta in Pucangan society.